THE IMPORTANCE OF USING INTERACTIVE METHODS IN BIOLOGY LESSONS - Esojanov , Azamatjon Vahidjon ugli (Educational Research in Universal Sciences, 2023)
There are very few studies concerning the importance of teaching methods in biology education and environmental education including outdoor education for promoting sustainability at the levels of primary and secondary schools and pre-service teacher education. The material was selected using special keywords from biology and sustainable education in several scientific databases. This article will be mainly argued about using interactive methods in biological science and in classroom for nowadays new generation. And it will be proved how this kind of methods influences for students education.